Transplant bioassay induces different imposex responses in two species of the genus Stramonita - Braga Castro, Ítalo (2012)
A bioassay to study differential specific responses in imposex development due to marine organotin pollution was done by transplanting specimens of the gastropods Stramonita haemastoma and Stramonita rustica from an imposex-free area to a marina with high marine traffic inside a ship repair yard, a place where local populations of S. haemastoma were known to show high indices of imposex. Three hundred sexually mature, imposex-free specimens of each species were kept in cages for 120 days, and samples of 30 individuals were periodically analysed for imposex development. Shell length, penis length and vas deferens development were recorded and imposex development indices (% imposex, RPLI and VDSI) were calculated. Our results indicated that imposex induction in S. haemastoma is faster and more sensitive than in S. rustica. Imposex incidence in S. haemastoma could be a useful tool for monitoring marine pollution by organotin compounds in harbours along the Brazilian coast.